Analisis Semiotika Pada Poster Film Leo (2023) Berdasarkan Teori Charles S. Peirce - Yosua Putra; Silvina Mayasari; Sari Ekowati Hadi (An Nafi': Multidisciplinary Science, 2025)
In the digital era, visual communication has become an inseparable element and one of the most effective tools for conveying messages in modern life. Movie posters are a common example of visual communication, serving as a medium to depict the essence of a film's story as well as an important commercial tool. This research analyzes the meaning of the Leo (2023) movie poster using Charles S. Peirce's semiotic theory. The aim is to uncover and elaborate on both the explicit and implicit meanings present in the film's poster. The method used is descriptive qualitative analysis with Peirce's semiotic approach, focusing on three main elements: object, representamen, and interpretant. Through the second trichotomy, the object is further divided into icon, index, and symbol. The results of the analysis show various important and hidden meanings within the poster. For instance, the lizard character in the center acts as the main focal point, hinting at the cause of Leo's panic. The school background in a tropical area, the RC (Remote Control) toy car rapidly and erratically controlled by Cole, and the discernible movement all contribute to the visual narrative. Additionally, symbols like the film's title and rating also convey important information. It can be concluded that the Leo (2023) poster effectively utilizes semiotic signs that can be elucidated using Charles S. Peirce's semiotic theory. This poster successfully serves as a concise and efficient medium for illustrating the overall content and ambiance of the film.